1984
DOI: 10.1037/0022-0663.76.6.1325
|View full text |Cite
|
Sign up to set email alerts
|

Componential modeling of alternative strategies for performing spatial tasks.

Abstract: Relations among aptitude, spatial task solution strategy, and task performance were explored through mathematical models of performance latency. Single-strategy and strategy-shifting models were tested individually for a stratified random sample of 30 male high school and college subjects. Different models fit different subjects on each of three task steps (encoding, synthesis, and comparison), suggesting that different subjects used different strategies for solving the same items. Some of the best fitting mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
1
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 10 publications
2
67
1
1
Order By: Relevance
“…Learners not only use different strategies for different problems but also shift strategies within a problem as a function of the difficulty characteristics of the task. These findings are consistent with other demonstrations of multiple strategies and strategy shifting in high school and college students (Kyllonen, Lohman, & Woltz, 1984;Ohlsson, 1984aOhlsson, , 1984bSnow, 1978Snow, , 1981. As Siegler and Campbell (1990) note:…”
Section: ·16·supporting
confidence: 80%
“…Learners not only use different strategies for different problems but also shift strategies within a problem as a function of the difficulty characteristics of the task. These findings are consistent with other demonstrations of multiple strategies and strategy shifting in high school and college students (Kyllonen, Lohman, & Woltz, 1984;Ohlsson, 1984aOhlsson, , 1984bSnow, 1978Snow, , 1981. As Siegler and Campbell (1990) note:…”
Section: ·16·supporting
confidence: 80%
“…In other words, the faster an individual can produce responses that contradict previously well-established verbal relations (by the wider community), the more flexible the behavior. Assessing relational flexibility may be particularly advantageous because flexibility is widely regarded as an important component of human cognitive abilities (e.g., Cattell, 1971;Kyllonen, Lohman, & Woltz, 1984;Premack, 2004).…”
Section: Participants Completed a Before/after And A Similar/differenmentioning
confidence: 99%
“…In other words, the faster an individual can produce responses that contradict previously well-established verbal relations (by the wider community), the more flexible the behavior. Assessing relational flexibility may be particularly advantageous because flexibility is widely regarded as an important component of human cognitive abilities (e.g., Cattell, 1971;Kyllonen, Lohman, & Woltz, 1984;Premack, 2004).On balance, the response latencies data obtained on inconsistent trials may provide a measure of not just relational flexibility but also the other variables mentioned above (e.g., processing speed). To obtain a relatively "pure" measure of relational flexibility, the effects of these extraneous variables need to be controlled.…”
mentioning
confidence: 99%
“…A process-analytic approach has been used to examine quantitative differences in observed performance as well as qualitative differences with regard to the strategies used by individuals on spatial processing tasks (Bethell-Fox, Cooper, 1975;Kyllonen, Lohman, & Snow, 1984;Kyllonen, Lohman, & Woltz, 1985;Lohman & Kyllonen, 1983;Pellegrino & Kail, 1981;Shepard & Feng, 1972;Shepard & Metzler, 1971;Sternberg & Weil, 1980). Snow (1978) found that performance could be accounted for by three types of strategy differences: the sequence in which processing steps are executed, the steps taken to solve problems, or summation differences where the organization of processing can vary within and between persons as well as across items on a task.…”
Section: Strategies and Information Processing Researchmentioning
confidence: 99%